2020
DOI: 10.3390/foods9091258
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and Effect of a Multistrain Starter Culture on Antioxidant and Rheological Properties of Novel Wheat Sourdoughs and Bread

Abstract: Food consumers make decisions primarily on the basis of a product’s nutritional, functional, and sensorial aspects. In this context, this study evaluated the persistence in sourdough of a multistrain starter culture from laboratory to bakery plant production and the effect of the starter on antioxidant and rheological properties of sourdoughs and derived bread. Lactobacillus sanfranciscensis B450, Leuconostoc citreum B435, and Candida milleri L999 were used as a multispecies starter culture to produce a sourdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 111 publications
0
14
0
Order By: Relevance
“…It has been largely demonstrated that lactic acid fermentation improves sensory characteristics, nutritional quality, texture and safety of starch-containing vegetables including cereals [ 7 ]. Strong scientific evidence support the beneficial effects of lactic acid bacteria fermentation in cereal matrices by enhancing the content and bioavailability of phenolic compounds, γ-aminobutyric acid (GABA) and antioxidant, anti-hypertensive and anti-inflammatory activities [ 8 , 9 , 10 ]. A number of recent investigations have evidenced that cereals are good fermentable substrates for lactic acid bacteria (LAB) that can be used as raw materials for development of probiotic beverages with enhanced nutritional properties [ 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been largely demonstrated that lactic acid fermentation improves sensory characteristics, nutritional quality, texture and safety of starch-containing vegetables including cereals [ 7 ]. Strong scientific evidence support the beneficial effects of lactic acid bacteria fermentation in cereal matrices by enhancing the content and bioavailability of phenolic compounds, γ-aminobutyric acid (GABA) and antioxidant, anti-hypertensive and anti-inflammatory activities [ 8 , 9 , 10 ]. A number of recent investigations have evidenced that cereals are good fermentable substrates for lactic acid bacteria (LAB) that can be used as raw materials for development of probiotic beverages with enhanced nutritional properties [ 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…commensal partner, which apparently neither elicit metabolic stress nor stimulation to F. sanfranciscensis, while the S. cerevisiae sourdough isolate rather showed competitive characteristics [23]. F. sanfranciscensis is in general nutrient competition with the S. cerevisiae, namely for maltose and sucrose, while the maltose-negative K. humilis prefers glucose [44]. Also, general mechanisms of redox-balance, e. g. thiol-metabolism, likely differ between yeast genera, and between F. sanfranciscensis strains, and may contribute to the strain-specific behavior observed [13,14].…”
Section: Discussionmentioning
confidence: 95%
“…In addition, lactic acid bacteria present in yogurt also provide healthy bioactive compounds with antioxidant properties and act as probiotics (Zhang et al, 2011). The positive effect of lactic acid bacteria is also observed in bread made with sourdought in which Sidari et al (2020) found that lactic acid bacteria is associated with the presence of phenolic compounds with antioxidant activity. Thus, yogurt is considered a food that must be part of a balanced diet throughout all stages of life.…”
Section: Introductionmentioning
confidence: 81%